Generalized Anxiety Disorder, panic disorder - diagnosis and treatment - Machaj, Dominik; Płaczek, Alicja; Cyboran, Katarzyna; Kuc, Monika; Białas, Filip (Journal of Education, Health and Sport, 2022)
Anxiety is one of the most common psychopathological symptoms. It is based on the feeling of a strong threat without triggering a real stimulus. They are often accompanied by somatic symptoms, making it difficult to function normally and carry out daily activities. The causes of anxiety disorders include genetic and environmental factors. Anxiety can take the form of, but is not limited to, generalized anxiety disorder and panic disorder, which are described below. We also distinguish phobia syndrome, obsessive-compulsive disorder, post-traumatic stress disorder, separation anxiety and selective mutism. Among the methods of treatment, we distinguish psychotherapy and pharmacotherapy.